Fiasko - Scheitern in der Frühen Neuzeit -- Beiträge zur Kulturgeschichte des Misserfolgs - Brakensiek, Stefan; Claridge, Claudia (Histoire, 2015)
This volume elaborates the mostly unwritten history of failure for the Early Modern period with case studies from English Studies, History, German Studies, and Theology.